(3GdJfHjg Ydi ef de jbY Hg ef aVdGA aGS Jfhjgs - (3CHh YHO Gddg eMeO Hf eMeO Hf eMeO Hf WGgQ Hf YjThf GdTQGW, GHf YjThf,J (B1109 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa Cgd MVQI bOSg hHYO , ajbhd GdedbH HGdTQGW Efi cfJ hVYJ JCdjakG ai GdJYQja HGdUGdMjf ef Cgd aGS , SejJg GdQhV GdYGWQ GdCfaGS HCNHGQ GdUGdMjf ef Ggd aGS s
(3BNQgG (B:s
(3hGdSjOI eMLhHI Yf jSGQ GdOGNd ddOQH COQcJgG JQYi eMHI SjOi YHO GdbGOQ GdLjdGfi hJfJSH Edjg Oaf GdKdGKI HGdOQH GdePchQ hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B65s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B683 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
Keywords: (3GdJGQjNs